The Effect of Leaflet Media Counseling To Increase Stunting Knowledge On Pregnant Women - Juliana Munthe (Institute of Computer Science (IOCS), 2021)
The prevalence of stunting globally in 2017 was 22.2% or around 150.8 million children under five in the world experienced stunting. Indonesia ranks fifth in the highest incidence of stunting after Pakistan (45%), Congo (43%), India (39%), and Ethiopia (38%). This study aims to analyze the effect of leaflet media counseling to increase knowledge of stunting on pregnant women. This type of research is experimental. The research design is a quasi-experimental with a time series design approach. The research design was pre-experimental (One group pre and post test design), namely research that used one group of subjects, measurements were carried out before and after treatment, namely the Effect of Leaflet Media Counseling to increase knowledge of pregnant women about stunting as many as 32 people. The results showed that there was an effect of leafleat media counseling to increase knowledge of stunting on pregnant women at Pematang Panjang Public Health Center with a p value of 0.001 < 0.05. It is hoped that health workers at Pematang Health Center will conduct counseling about stunting in toddlers so that the growth and development of children is in accordance with their age.